Prime minister and cabinet - Buckley, Stephen (Edinburgh, 2006)
This introduction to the workings of the Prime Minister and Cabinet is written in light of major recent events and issues such as the war with Iraq, the Hutton Inquiry, the Butler Report, the Blair-Brown relationship, and continuing problems relating to Europe. This insightful volume gives readers an overview of the Blair premiership and the workings of a Labour Cabinet at a time when both are facing increased criticism and pressure.
Keywords: Cabinet